2016
DOI: 10.7752/jpes.2016.03156
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Purpose: to work out program of differentiated correction of 6-10 years' age schoolchildren's postures by means of physical education. Material: At initial stage (medical examination) 216 schoolchildren (girls and boys of 6-10 years' age) were examined. In children, who had no visible posture disorders, (n=156) we registered indicators of bioelectrical activity of back skeletal muscles on both sides of backbone. For this purpose we used method of surface electromyography. In the next stage 107 children of prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Children with low level of motor skills are not selfassured and inclined to avoid physical activity (Chen & Housner, 2013;Nosko, Razumeyko, Iermakov, & Yermakova, 2016). Modeling is one of the methods of studying of physical training process efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Children with low level of motor skills are not selfassured and inclined to avoid physical activity (Chen & Housner, 2013;Nosko, Razumeyko, Iermakov, & Yermakova, 2016). Modeling is one of the methods of studying of physical training process efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the methods of multivariate analysis for these purposes were not used, and therefore the creation of the algorithm for the completion of teams in aerobic exercise is the first developed problem. The analysis of literary data (Arziutov, G., Iermakov, S., Bartik, P., Nosko, M., & Cynarski, W. J., 2016;Boichuk, R., Iermakov, S., & Nosko, M., 2017;Kriventsova, I., Iermakov, S., Bartik, P., Nosko, M., & Cynarski, W. J., 2017;Nosko, M., Razumeyko, N., Iermakov, S., & Yermakova, T., 2016;Osipov, A. Y., Kudryavtsev, M. D., Iermakov, S. S., & Jagiełło, W., 2017) showed that most authors in determining the basic principles of constructing a training process one of the main consider the principle of combining team training and individualization. At the same time, if cyclic and gaming sports already have some work on specific recommendations for the construction of a training process for each team (Pomeshchikova, I., Iermakov, S., Bartik, P., Shevchenko, O., Nosko, M., Yermakova, T., & Nosko, Y., 2016;Zhanneta, K., Irina, S., Tatyana, B., Olena, R., Olena, L., & Anna, I., 2015), then sports aerobics is just beginning to develop the theoretical, methodological and organizational foundations of the unity of team and individual approach to the training process of athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, from this point of view, our work represents a certain novelty. It should be noted, however, that some authors (Nosko, M., Razumeyko, N., Iermakov, S., & Yermakova, T., 2016) try to give an integral assessment of individuality, taking into account a wide range of indicators. These indicators include the properties of the nervous system in conjunction with the predominance of one of the cognitive types and the development of certain physical qualities and psychophysiological abilities.…”
Section: Discussionmentioning
confidence: 99%
“…(Kostyuchenko & Orekhov, 2010). Recent studies have found the persistent health deterioration trend in the student communities in Russia (Bal'sevich, 2010), and it is natural that a special emphasis is now made on the young people's physical activity encouragement initiatives (Lubysheva, 2012) viewed by researchers and analysts as pivotal for the health protection and improvement; non-medical disease prevention (Garkusha, 2014;Skead & Rogers, 2016); muscular imbalance correction (Aftimichuk & Varvarich, 2013;Nosko, Razumeyko, Iermakov, & Yermakova, 2016); body adaptability increasing (Vitun, 2009;Kolokoltsev, Buykova, & Bulnaeva, 2017); and life prolongation (Blair, Cheng, & Holder, 2001; initiatives. Students have long been ranked on top of the health risk groups vulnerable to many diseases due to high academic loads and associated neuro-psychic stresses (Abdullina, 2014;Lebedinsky, & Kolokol'tsev, 2016); physical inactivity (Prosvirina, Kolokoltsev, Kolchanova, Cieslicka, & Stankiewicz, 2015); and poor if any motivations for healthy lifestyles (Hortigüela-Alcalá, Pérez-Pueyo, & Moncada-Jiménez, 2015;Gavrilik, 2016).…”
Section: Introductionmentioning
confidence: 99%